Delayed decrease of excitatory amino acid neurotransmitters in parietotemporal cortex and hippocampus after complete cerebral ischemia in aged rats - Müldner, Albrecht; Hoyer, Siegfried (Archives of gerontology and geriatrics, 1997)
A 15-min period of complete cerebral ischemia (CCI) was used in aged rats to investigate changes in tissue contents of the amino acid neurotransmitters (AANT) glutamate (glu), aspartate (asp), gamma aminobutyric acid (gaba) and glycine (gly) in parietotemporal cortex and hippocampus during ischemia and up to 96 h of postischemic recirculation. The AANT were determined by HPLC. The excitatory AANT glu and asp showed a first decrease at the end of CCI in hippocampus and after 1 h of postischemic recirculation in parietotemporal cortex, reflecting a release of these AANT into the extracellular space with a further loss into the blood. A second decrease in glu and asp was seen after 24 h of postischemic recirculation in hippocampus and after 48 h in parietotemporal cortex. This coincides with previously described disturbances in energy metabolism from 24 h to 96 h in hippocampus and from 48 h to 72 h in parietotemporal cortex in the same experimental model in aged rats. This might be a causal factor in delayed postischemic neuronal damage. A comparison with investigations in young animals reveals an enhanced decrease of glutamate and aspartate tissue contents during the postischemic recirculation period in old rats indicating an enhanced release of these amino acid neurotransmitters. A significant decrease of gaba tissue content seen in hippocampus at 48 h and 72 h of postischemic recirculation with subsequent disproportion of inhibitory AANT (lower) to excitatory AANT (higher) might reflect a greater vulnerability of hippocampus than of parietotemporal cortex to ischemia. A significant decrease in the NMDA-receptor coactivator gly in parietotemporal cortex at the end of CCI and at 48 h, 72 h, and 96 h of postischemic recirculation, which was not seen in hippocampus, might be another reason for higher vulnerability of hippocampus to ischemia.